The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.surg.2012.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Novel withanolides target medullary thyroid cancer through inhibition of both RET phosphorylation and the mammalian target of rapamycin pathway

Abstract: Background Despite development of current targeted therapies for medullary thyroid cancer (MTC), long-term survival remains unchanged. Recently isolated novel withanolide compounds from Solanaceae physalis are highly potent against MTCs. We hypothesize that these withanolides uniquely inhibit RET phosphorylation and the mammalian target of rapamycin (mTOR) pathway in MTC cells as a mechanism of antiproliferation and apoptosis. Methods MTC cells were treated with novel withanolides and MTC-targeted drugs. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Preliminary results revealed 1 as a promising chemotherapeutic candidate for antitumor therapy, and that further translational evaluation of 1 was warranted (Grogan et al 2013; Samadi et al 2012). However, difficulties arose in obtaining sufficient quantities of V. breviflora biomass needed to isolate the required amounts of 1 for such studies.…”
Section: Withanolides Isolated From Natural Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary results revealed 1 as a promising chemotherapeutic candidate for antitumor therapy, and that further translational evaluation of 1 was warranted (Grogan et al 2013; Samadi et al 2012). However, difficulties arose in obtaining sufficient quantities of V. breviflora biomass needed to isolate the required amounts of 1 for such studies.…”
Section: Withanolides Isolated From Natural Sourcesmentioning
confidence: 99%
“…Furthermore, mechanistic studies showed that 1 inhibits proliferation by inducing a dose-dependent G2/M cell cycle arrest while promoting cell death through both intrinsic and extrinsic apoptotic pathways (Grogan et al 2013; Samadi et al 2009; Samadi et al 2010; Samadi et al 2012). …”
Section: Antiproliferative Evaluation Of Withanolide Librarymentioning
confidence: 99%
“…This kinase inhibitor showed inhibitory effects on both MZ-CRC and TT cell proliferation, although no effects on RET autophosphorylation were observed, suggesting that the PI3K/mTOR activation is not RET related in this specific cell line. Novel experiments with anolide derivatives have also demonstrated an inhibitory effect on RET phosphorylation as well as on the mTOR signalling in MTC-TT and DRO 81-1 cells (50). The fact that RET activation stimulates mTOR signalling could imply that the observed inhibition of mTOR signalling is the direct result of the inactivation of RET.…”
Section: Monotherapymentioning
confidence: 99%
“…2004; Akeno-Stuart et al 2007; Brandt et al 2010; Konings et al 2010; Samadi et al. 2012; Frett et al 2014; Sun et al 2014; Schwartz et al 2015; Dunna et al.…”
Section: Novel Investigational Tkis With Activity Against Retmentioning
confidence: 99%